Analisis Kecenderungan Pemberitaan Kampanye Calon Presiden 2019 di Antaranews.com - Andam Rukhwandir; Tatik Yuniarti (Fakultas Komunikasi, Sastra, dan Bahasa, 2020)
This study discusses the balance of the 2019 presidential election campaign coverage on Antaranews.com. This research uses a quantitative approach with descriptive content analysis method which is carried out through coding techniques on the news that has been determined as a sample in the study. The research was conducted by coding news samples through Westerstahl's objectivity theory. The objectivity of news can be measured through this theory, which has two dimensions, namely, factuality and impartiality. Coding is done by analyzing the sentences in the news through these dimensions which are divided into several indicators. The results of the study found that there was a tendency for the 2019 presidential candidates to report on Antaranews.com. The news on the presidential candidates on Antaranews.com tended to be more towards Joko Widodo. This is evident in Jokowi's reporting, which tends to show more positive opinions and a larger portion of the coverage.